Pelatihan Debat dalam Bahasa Inggris untuk Siswa SMA PGRI 6 Banjarmasin - Nurfitriah Nurfitriah; Muhammad Amril Asy'ari; Ria Adriyati; Suwaji Suwaji (Politeknik Negeri Banjarmasin, 2019)
PGRI 6 High School (SMA) Banjarmasin has common problems related to the availability of human resources and competencies to be able to manage extracurricular activities in English, especially for debating, hence students from this school have never participated in related competition activities at the local or national level. The English teaching teachers at this school are highly motivated to send representatives of students to take part in the debate competition but they have difficulties to begin preparations for this debate competition. They do not know how the recruitment and selection process for students to debate, nor have the expertise and knowledge about debate and there is no budget for the whole series of student debating activities. Banjarmasin State Polytechnic as one of the state universities in South Kalimantan which already has a well-known name in the English language debate level at local, regional and national level offers a solution to the problems of extracurricular activities in the form of debate training in English for high school students of PGRI 6 Banjarmasin. This community service activity aims to initiate extracurricular activities and improve the ability to debate in English for students of PGRI 5 Banjarmasin High School. The targeted output is the formation of a forum for partner school students to improve their English skills through debate and the selection of student representatives to participate in the debate competition. The teachers of English are expected to have knowledge of managing English extracurricular debate activities after joining the training.